Evaluation of molecular methods to improve the detection of Burkholderia pseudomallei in soil and water samples from Laos. - Knappik, M; Dance, D; Rattanavong, S; Pierret, A; Ribolzi, O; Davong, V; Silisouk, J; Vongsouvath, M; Newton, P; Dittrich, S (American Society for Microbiology, 2015)
Burkholderia pseudomallei is the cause of melioidosis, a severe and potentially fatal disease of humans and animals. It is endemic in northern Australia and Southeast Asia and is found in soil and surface water. The environmental distribution of B. pseudomallei worldwide and within countries where it is endemic, such as the Lao People's Democratic Republic (Laos), remains unclear. However, this knowledge is important to our understanding of the ecology and epidemiology of B. pseudomallei and to facilitate public health interventions. Sensitive and specific methods to detect B. pseudomallei in environmental samples are therefore needed. The aim of this study was to compare molecular and culture-based methods for the detection of B. pseudomallei in soil and surface water in order to identify the optimal approach for future environmental studies in Laos. Molecular detection by quantitative real-time PCR (qPCR) was attempted after DNA extraction directly from soil or water samples or after an overnight enrichment step. The positivity rates obtained by qPCR were compared to those obtained by different culture techniques. The rate of detection from soil samples by qPCR following culture enrichment was significantly higher (84/100) than that by individual culture methods and all culture methods combined (44/100; P < 0.001). Similarly, qPCR following enrichment was the most sensitive method for filtered river water compared with the sensitivity of the individual methods and all individual methods combined. In conclusion, molecular detection following an enrichment step has proven to be a sensitive and reliable approach for B. pseudomallei detection in Lao environmental samples and is recommended as the preferred method for future surveys.